RESEARCH ON THE INCLUSIVE EDUCATION ADAPTABILITY OF VISUALLY IMPAIRED COLLEGE STUDENTS IN CHINA - bo, zhou; Eng Hock, Kway (South Asian Journal of Social Sciences and Humanities, 2024)
The education of visually impaired students in China has also gone through a developmental stage from "segregated education" to "special education" and then to "inclusive education". In this paper, we take the visually impaired students at Binzhou Medical College, the first university in China to provide higher education for the disabled, as the research object. The study was carried out to investigate the adaptability of visually impaired students, using various research methods such as literature review method, questionnaire method and case study method, we investigated and researched the adaptation of visually impaired students to inclusive education from several aspects such as quality of life, social support, mental health level, self-esteem and self-efficacy study. Finally, the study proposed several countermeasures and suggestions, such as attaching importance to the physical and psychological rehabilitation of visually impaired students, emphasising the inclusive of education and rehabilitation, strengthening the training of professional teachers for visually impaired students, emphasising the complementarity between schools and professions, and improving the employment support service system for visually impaired students, which are of great significance in promoting the development of the cause of inclusive education for visually impaired students and improving the adaptability of inclusive education for visually impaired students.
Keywords: Visually Impaired College Students; Inclusive Education; Adaptability